KELAYAKAN ORNAMEN MAHAR PENGANTIN DARI LIMBAH ALUMINIUM FOIL - pratiwi, bias nurul; Ihsani, Ade Novi Nurul; Amira, Dini (Fashion and Fashion Education Journal, 2021)
Aluminum foil has the characteristics of being strong, lightweight, heat-resistant and does not contain macnet, is one type of metal that is often found in everyday life. The suitable color is made of aluminum foil suitable for ornamental raw materials. The purpose of this research: to study how the validity of the products and the feasibility of dowry ornaments from aluminum foil waste. The research method is an experimental method. The technique of taking data using a questionnaire or questionnaire. The analysis technique uses descriptive percentages. The dowry ornament sensory test results from aluminum foil waste obtained a value of 74% with good answers, with the highest value possible in the color indicator. Based on the favored test dowry ornament from aluminum waste obtained 87% value with a very like answer. Conclusion: bridal dowry ornaments made from aluminum foil waste were declared feasible and valid through sensory testing by expert panelists and were declared very fond through the preference test.